(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
The neurodegenerative condition known as Alzheimer’s disease (AD) impairs cognitive function and produces dementia in older people. The disease’s precise mechanism is still a mystery. Four drugs are available. However, they all have a long list of adverse effects and only help people with their warning signs. Medicinal chemists are searching for ways to treat this disease. There is discussion about creating and using a new class of multifunctional small molecule inhibitors. The hydrazone scaffold was used to create a wide range of chemicals. This is because hydrazone derivatives may disrupt the self-assembly of amyloid beta (A), one of the factors that cause fibrils and oligomers. They may also reverse the effects of harmful compounds like free radicals on effective therapeutic agents like medications that penetrate the central nervous system. Structure-based drug design methods were used in this investigation. A protein target (code ID 4EY7) was selected based on published literature research and factors like a lower resolution value (2.35), no mutation, Homo sapiens, and the X-ray diffraction technique. Fifteen Hydrazone derivatives with increased interactions, higher binding scores, and improved drug-like properties and drug kinetic parameters were designed using the protein target, engineered to interact with compounds of interest (a lead compound with a higher binding energy). Promising pharmacotherapeutic drugs for AD treatment may be developed using the results of these investigations.